Synthesis and Characterization Double Perovskite Compound Sr2Mg1-xMnxMoO6-δ by Sol Gel Method - MATURAMA (NIM 10503061), DICKY
The anode material in solid oxide fuel cell has to have high electric conductivity, catalytic effect for hydrogen decomposition from hydrocarbon and good resistant to sulfur. For these purposes, anode material based on double perovskite structure, A2BBÃƒÂ‚Ã‚Â’O6 is developed. In this study, double perovskite compounds, Sr2Mg1-xMnxMoO6- (SMMO) with x = 0.2, 0.5, 0.8, and 1, were synthesized by means of sol-gel method at 1350οC. The structure of the crystals was characterized using X-rays diffractometer. The results of diffraction were analyzed by Le Bail method using Rietica program. The oxides have monoclin structure and the space group was P 21/n. The lattice parameters as well as the unit-cell volume are increased with x. Meanwhile the DC measurement for electrical conductivity as a function of temperature showed that Sr2Mg0,2Mn0,8MoO7 has the highest value of conductivity.